(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
The rapid development of electric vehicles in the automotive industry opens the door for the development of DC-DC converters. This paper proposes a high-gain DC-DC converter with a lower part count for light electric vehicle (LEV) applications. When the converters are cascaded for maximum gain, a topology change is recommended that involves the integration of a voltage multiplier and a switching capacitor with a quadratic boost structure. A remarkable 496 is offered by this converter. Additionally, the theoretical portion of this work covers the 496 performance of the presented converter. Furthermore, MATLAB/Simulink is utilized to simulate the proposed configuration, which confirms the theoretical findings, and a 100 W laboratory prototype of the same is fabricated and tested to verify the performance of the presented converter.